Naukowe biografie twórców i kryteria ich poprawności albo głos w obronie biografii „nienaukowych” - Szmidt, Krzysztof J. (Biograficzne badania nad twórczością. Teoria i empiria, 2016)
The article consists of several parts, the first of which is devoted to the criteria according to which scientific biographies are assessed and what differentiates them from popular or artistic biographies. Based on the characteristic of works in the field of creative psychobiography, the author describes four main criteria of a scientific biography (theoretical, methodological, narrative and heuristic one) and against this background, in the following part of the article, he goes on to presenting the main motives of creating artistic biographies of creators (the motive of filling in the missing parts, the motive of “fresh” interpretation, the motive of synthesis and the motive of discovery). In the summary, he compares the situation of authors of a creative biography – a scientist and an artist, thus praising the “non-scientific” biographies.